Chronic kidney disease as a risk factor for acute community-acquired infections in high-income countries: a systematic review. Issue 4 (17th April 2014) - McDonald, Helen I; Thomas, Sara L; Nitsch, Dorothea
Abstract : Objective: A systematic review of the association of predialysis chronic kidney disease (CKD) with the incidence of acute, community-acquired infections. Design: We searched the MEDLINE, EMBASE and Cochrane databases (inception to 16 January 2014) for studies analysing the association of predialysis kidney disease with the incidence of acute, community-acquired urinary tract infection (UTI), lower respiratory tract or central nervous system infections or sepsis. Studies were required to include at least 30 participants with and without kidney disease. Setting and participants: Community-based populations of adults in high-income countries. Outcome measures: Acute, community-acquired UTI, lower respiratory tract or central nervous system infections or sepsis. Results: We identified 14 eligible studies. Estimates from two studies lacked 95% CIs and SEs. The remaining 12 studies yielded 17 independent effect estimates. Only three studies included infections managed in the community. Quality assessment revealed that probable misclassification of kidney disease status and poor adjustment for confounding were common. There was evidence from a few large high-quality studies of a graded association between predialysis CKD stage and hospitalisation for infection. One study found an interaction with age, with a declining effect of CKD on infection risk as age increased. There was evidence of between-studies heterogeneity (I 2 =96.5%, p<0.001) which persisted in subgroup analysis, and thus meta-analysis was not performed. Conclusions: Predialysis kidney disease appears to be associated with increased risk of severe infection. Whether predialysis kidney disease increases the susceptibility to infections and whether age modifies this association remains unclear.